Ruthenium Imidazophenanthrolinium Complexes with Prolonged Excited‐State Lifetimes. Issue 23 (14th July 2015) - Staehle, Robert; Reichardt, Christian; Popp, Jürgen; Sorsche, Dieter; Petermann, Lydia; Kastner, Katharina; Streb, Carsten; Dietzek, Benjamin; Rau, Sven
Abstract: A series of ruthenium polypyridyl complexes [Ru(tbbpy)3 ][PF6 ]2 (0, tbbpy = 4, 4′‐di‐ tert ‐butyl‐2, 2′‐bipyridine), [Ru(tbbpy)2 (bbip)][PF6 ]3 {1, (bbip)Br = 1, 3‐(bisbenzyl)‐1 H ‐imidazo[4, 5‐ f ][1, 10]phenanthrolinium bromide}, [Ru(tbbpy)(bbip)2 ][PF6 ]4 (2 ), and [Ru(bbip)3 ][PF6 ]5 (3 ) were synthesized. The new complexes2 and3 were fully characterized, and their X‐ray crystal structures, absorption and emission spectra, quantum yields of emission, and cyclic voltammograms were determined. Within this series, a trend towards increased lifetime and quantum yields of emission can be observed, especially in the presence of oxygen. The location of the first excited state on the imidazophenanthrolinium ligands has been elucidated by resonance Raman spectroscopy of1 and3, which revealed that the energy of the π* orbitals of the bbip ligands is lower than that of the π* orbitals of the tbbpy ligand. Abstract : A series of ruthenium polypyridyl complexes containing an imidazolium‐functionalized phenanthroline ligand are presented. The complexes are fully characterized, and their solid‐state structures are determined. The influence of the new ligand is investigated through absorption and emission spectroscopy, cyclic voltammetry, and resonance Raman spectroscopy investigations.